Efek Pemberian Reward dan Punishment terhadap Performance Karyawan - Feby Kurnia; Gunawan, Ahmad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
In order for a company to be a place where people are continuously growing, it needs its employees to perform well and be motivated to work hard. There are numerous approaches to raising worker productivity. Rewarding employees when they achieve their goals and punishing them for carelessness at work are the best ways to raise employee performance. One strategy the company uses to constantly inspire its staff to perform at the highest level for the company is to give them rewards or penalties. This system of rewards and penalties is in place to keep pushing workers to deliver quality work.